A informatização do cotidiano: reflexões sobre o monitoramento por câmeras de vigilância na cidade de São Carlos - SP - Verardino, Tiago [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The introduction of new technologies in the security sector, displayed in the daily life of the city of São Carlos - State of São Paulo, points to several reflections on the actions of the current technical phenomenon. The monitoring of behaviors through surveillance cameras that is enabled by the technological advancements in the security sector, is one of the many activities that pervade the computerization of everyday life. This way, the human corporeality becomes a materially sensitive certainty face the complexity of realization in the space, revealing the fragility of the relation between place and world. The choice of the monitoring through surveillance cameras consists in the possibility to demonstrate how these technical objects perform in the geographical space, through social interactions, pointing to situations that highlight the fragility in their use starting from their primary character of creation. The diffusion of information and the possibility of a technical standardization concerning the monitoring by cameras e the creation of databases containing the collected images also demonstrate the expansion of a new vector of capital in urban spaces, the providers of private surveillance services. As a form of counter rationalization of space, understood as medium, condition and product of the relations of capitalist production, we expose the everyday life also as a possibility of reaching new meanings for places. We believe that through the manifestation of the geographical space as a banal space, e.g. everybody's space, new forms of work and struggle can result from the confrontation of the predatory character that these technical objects offer to the rational use of the space to the capitalist accumulation

A introdução de novas tecnologias do setor de segurança, manifestadas no cotidiano de São Carlos - SP, aponta para algumas reflexões quanto as ações do fenômeno técnico atual. O monitoramento de comportamentos, através de câmeras de vigilância, possibilitado pelos avanços tecnológicos do setor de segurança, é uma das inúmeras práticas que permeiam a informatização do cotidiano. Assim, a corporeidade humana torna-se uma certeza materialmente sensível diante da complexidade de realização do e no espaço, revelando a fragilidade da relação entre lugar e mundo. A escolha pelo monitoramento através de câmeras de vigilância consiste na possibilidade de demonstrar como estes objetos técnicos, através das interações sociais, atuam no espaço geográfico, apontando situações que realçam a fragilidade do uso destes a partir de seu caráter primário de criação. A difusão da informação e a possibilidade de uma padronização técnica quanto ao monitoramento por câmeras e criação de bancos de dados das imagens registradas também demonstra a expansão de um novo vetor do capital nos espaços urbanos, o setor de serviços da vigilância privada. Como forma de contra racionalização do espaço, compreendido como meio, condição e produto das relações de produção capitalista, expomos o cotidiano, também, como possibilidade do encontro de novos significados dos lugares. Acredita-se que através da manifestação do espaço geográfico como espaço banal, ou seja, o espaço de todos, novas formas de trabalho e luta poderão surgir ao enfrentamento do caráter predatório que oferecem estes objetos técnicos ao uso racional do espaço à acumulação capitalista
Keywords: Geografia urbana; Sistemas de segurança; Cameras eletronicas; Vigilância eletrônica; Espaço em geografia; Espaços públicos; São Carlos (SP)